Comparison of blood pressure values and expression of genes associated with hypertension in children before and after hematopoietic cell transplantation - Wojciech Strojny; Kinga Kwiecińska; Kamil Fijorek; Michał Korostyński; Marcin Piechota; Walentyna Balwierz; Szymon Skoczeń (Scientific Reports, 2021)
Abstract Hypertension is a well-known late effect of hematopoietic cell transplantation (HCT), but no markers predicting its development are known. Our aim was to assess short-term blood pressure (BP) values and expressions of hypertension-associated genes as possible markers of hypertension in children treated with HCT. We measured systolic blood pressure (SBP) and diastolic blood pressure (DBP), using both office procedure and ambulatory BP monitoring (ABPM) in children before HCT and after a median of 6 months after HCT. We compared the results with two control groups, one of healthy children and another of children with simple obesity. We also performed microarray analysis of hypertension-associated genes in patients treated with HCT and children with obesity. We found no significant differences in SBP and DBP in patients before and after HCT. We found significant differences in expressions of certain genes in patients treated with HCT compared with children with obesity. We concluded that BP values in short-term follow-up after HCT do not seem to be useful predictors of hypertension as a late effect of HCT. However, over expressions of certain hypertension-associated genes might be used as markers of hypertension as a late effect of HCT if this is confirmed in larger long-term studies.